The Politics of Identity: The History of African Americans Reconsidered through Narratives - Pun, Min (Journal of Political Science, 2017)
The narratives are a means of sharing each other's experiences, linking people in time and event over the generations. As such are the narratives of African Americans who have the stories of slavery and freedom that helped them to form their identity as Americans. Thus, the present paper attempts to shed light on the definitions of identity politics and how African Americans come across the experience of slavery, reconstruct their shared history and ultimately attain their identity in the mainstream American life. Journal of Political Science. Vol. 17, 2017, Page: 52-62